Theoretical Foundations of Africa’s Economic Transformation and Growth - Atta-Mensah, Joseph (Scientific Research, 2017)
This paper provides the theoretical underpinnings of growth models to explain structural economic transformation in Africa. The paper suggests that endogenous growth model is the key for understanding long-run growth of economies through the accumulation of knowledge. Private and public investments in knowledge and Research and Development (R & D) have longrun effects on growth. Since small changes in the growth rate of an economy can cumulate into large changes in the standard of living over a generation or more, government policies can have a large impact on economic welfare. Furthermore, endogenous growth models provide a richer structure that can add insight into the mechanics of growth. The implications of the growth models examined in this paper are that for an African country to achieve economic transformation through an interrelated processes of structural change that accompany economic development, and growth has to be at sustainable high levels for a very long time. Furthermore, it is important African policymakers work hard to circumvent diminishing marginal productive of key factors of production. It is also important that adequate resources are invested by African government in research and development, allowing for technological progress, innovations and accumulation of knowledge. A combination of these factors is the necessary ingredient for sustainable high levels of growth. The endogenous growth models hold a lot of promise for the structural economic transformation of African economies. The paper offers policy advice for African countries attempting to transform and build resilient economies.
Keywords: Structural Economic Transformation; Growth Models; Policy Advice